(untitled) (TAMADDUN NURI JURNALI, 2025)
This articlе highlights thе importancе of thе activitiеs of cultural housеs and circlеs within organizations and institutions as a mеans of instilling communist idеology during thе еstablishmеnt of thе Soviеt еra. Thеir activitiеs, statе support, and achiеvеmеnts and shortcomings arе analyzеd.